Understanding the Circulation Mechanism of Hydro Geothermal System in China: Circulation Mechanism of Hydro Geothermal System - Bannya, Roksana (IJRDO-Journal of Applied Science, 2019)
The present study focuses on hydro geochemical characteristics and circulation mechanism of deep geothermal water in study area. Isotopic and chemistry methods have been employed to enrich the study of the geothermal system. An emphasis is put on the estimation of the exchange temperature in the deep reservoir and the residence time of the geothermal waters. A total of 23 water samples were collected, which included 13 hot water samples and 10 cold water samples. The temperature range of cold water is between 25.2 to 28.5℃, and the pH values are nearly neutral. Hydrochemical type of cold waters is mainly HCO3-Ca or HCO3·Cl- Na·Ca. Hot water temperature ranges from 42.0 to 92.7°C, and the pH is weakly alkaline. There is a trend in the hydrochemical type of hot waters which shows a change from HCO3·Cl-Na·Ca to Cl-Na type from inland to coastal areas within the studied area. We believe that Na-K-Ca geothermometer results are more accurate, and the average exchange temperature is estimated to be 171.9 °C. The hot water’s circulation depths are between 105.4 to 2329.6 m. The cold water ratio in the mixed waters is in a range of 21% ~ 89%.